2016
DOI: 10.1007/s40620-016-0327-0
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound findings of BK polyomavirus-associated nephropathy in renal transplant patients

Abstract: BK polyomavirus (BKV) is an emerging pathogen in immunocompromised patients. BKV infection occurs in 1-9 % of renal transplants and causes chronic nephropathy or graft loss. Diagnosis of BKV-associated nephropathy (BKVAN) is based on detection of viruria then viremia and at least a tubule-interstitial nephritis at renal biopsy. This paper describes the ultrasound and color Doppler (US-CD) features of BKVAN. Seventeen patients affected by BKVAN were studied using a linear bandwidth 7-12 MHz probe. Ultrasound sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…Sharma et al [ 11 ] analyzed 6017 ultrasonic scans performed in 614 patients with 462 episodes of acute rejection from 1992 to 2000, and reported that a >10% increase over the previous ‘best’ RI had a sensitivity of 60% and a specificity of 90% for the diagnosis of acute rejection. Dugo et al [ 13 ] found that ultrasound showed typical hypoechoic lesions with irregular edges in the cortex of BKVAN patients, suggesting that ultrasound can be useful for the non-invasive diagnosis of BKVAN when combined with blood and urine screening tests. Cano et al [ 14 ] reviewed the literature from the past 10 years and concluded that an elevated RI is an early predictor of histologically relevant chronic allograft nephropathy.…”
Section: Discussionsupporting
confidence: 85%
“…Sharma et al [ 11 ] analyzed 6017 ultrasonic scans performed in 614 patients with 462 episodes of acute rejection from 1992 to 2000, and reported that a >10% increase over the previous ‘best’ RI had a sensitivity of 60% and a specificity of 90% for the diagnosis of acute rejection. Dugo et al [ 13 ] found that ultrasound showed typical hypoechoic lesions with irregular edges in the cortex of BKVAN patients, suggesting that ultrasound can be useful for the non-invasive diagnosis of BKVAN when combined with blood and urine screening tests. Cano et al [ 14 ] reviewed the literature from the past 10 years and concluded that an elevated RI is an early predictor of histologically relevant chronic allograft nephropathy.…”
Section: Discussionsupporting
confidence: 85%
“…Despite heterogeneous parenchymal distribution compounded by the prominent inflammatory reactions, serial biopsies in PyVAN demonstrate overall progression of fibrosis. In this context, the contribution of PyVAN to graft loss due to development of graft sclerosis cannot be underestimated .…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, published imaging features associated with polyomavirus nephropathy include a streaky pattern of alternating hypoechoic bands at grayscale US with increased RIs in the renal arteries at Doppler interrogation, signifying nonspecific nephritis (Fig 14). At contrast-enhanced CT, this may appear as areas of streaky or wedgelike hypoenhancement extending from the papilla to the cortex (118,119). However, as a result of continued immunosuppression, these patients remain at increased risk for opportunistic pathogens such as Nocardia and fungal organisms such as Aspergillus and Mucor species.…”
Section: Infectious Complicationsmentioning
confidence: 99%